Cryptic genetic variation uncovers evolution of environmentally sensitive parameters in Caenorhabditis vulval development. Issue 5 (20th August 2014) - Grimbert, Stéphanie; Braendle, Christian
SUMMARY Understanding the robustness of developmental systems requires insights into the sensitivity of underlying molecular and cellular parameters to perturbations, and how such sensitivity evolves. We address these issues using vulval cell fate determination—a reproducible and robust patterning process regulated by a cross‐talk of EGF‐Ras‐MAPK and Delta‐Notch pathways. Although the final vulval cell fate pattern is identical in all Caenorhabditis species, the patterning process underlies extensive cryptic genetic variation between and within species. Here, we tested whether this cryptic genetic variation translates into variation in developmental sensitivity to environmental perturbations. We disrupted vulval patterning using thermal perturbations to quantify and compare environmental sensitivity of different system parameters between distinct genotypes of C. elegans and C. briggsae. Thermal perturbations globally debuffered vulval development, triggering diverse pattering variants, whose frequency and spectra were strongly species‐ and genotype‐dependent. This condition‐dependent variation indicates that environmental sensitivity of different system properties, such as vulval competence or vulval induction, is subject to evolutionary change. High temperature induced a genotype‐specific decrease of secondary fate induction and corresponding Notch pathway activity in the C. elegans N2 strain; in contrast, hypoinduction of the primary cell fate was never observed. Vulval precursor cells therefore differ in temperature sensitivity and such cell‐specific sensitivity shows evolutionary variation. We further compared spectra of temperature‐induced vulval variants to the ones induced by mutation accumulation in the same genotypes. In response to either perturbation, we observed similar genotype‐dependence of variant production, allowing identification of distinct system features most sensitive to both mutation and environment. Taken together, we show how sensitivity of system parameters regulating Caenorhabditis vulval development depends on subtle interactions between perturbations and genetic background. Our results imply that cryptic genetic variation may reflect evolutionary variation in developmental robustness, therefore potentially contributing to the maintenance of phenotypic precision when facing perturbations.